ANALISIS HUBUNGAN HEALTH BELIEF MODEL DENGAN SAFETY BEHAVIOUR PADA PEKERJA DI PT INDONESIA POWER UNIT PLTU BANTEN 3 LONTAR OMU TAHUN 2022 - Afifah Thiya Aisyahdian (2023)
PT Indonesia Power Unit PLTU Banten 3 Lontar OMU engaged in electricity has potential dangers. Based on data obtained from companies over the past 4 years, there are 39 near misses and 200 unsafe conditions that can cause work accidents. Therefore, it is important to apply safety behavior. This study aims to analyze the relationship of the Health Belief Model to safety behaviour in workers at PT Indonesia Power Unit PLTU Banten 3 Lontar OMU. This research uses quantitative methods with cross-sectional research designs. The total population in this study was 442 workers and the total sample was 114 workers with sampling techniques using quota sampling techniques. Result from research shows that of the 6 dimensions of the Health Belief Model that has been studied, there is 1 dimension that has a relationship with safety behavior, namely perceived barriers (p-value = 0.025). Based on the results of the research obtained, it is hoped that the company will be able to increase the knowledge of workers so that they have a change in perception regarding the importance of implementing safety behavior so that there is no increase in perceived barriers for workers.